A mechanical model to estimate legs muscle stiffness coefficients in horse during jumping - Shahbazi-Moghaddam, M.; Khosravi, N. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
The purpose of present study was to use a simple mechanical model to estimate horses` legs muscles stiffness coefficients in jump height during jumping a spread fence of 140 cm high. A digital camcoder was used (25 Hz) along with Ulead Studio program in order to obtain time, related distance, and various angles in horses` legs data. The total jump distance and time of flight for each horse were measured with a precision of 10 -2 m and 10 -2 s respectively. Biomechanical formulae have been established in order to evaluate the muscles stiffness coefficients. Three groups of leg muscles; serratus ventralis, biceps brachii, and radial carpal extensor were considered in this study and their stiffness coefficients were successfully estimated.